Xylotomic similarities and natural habitat of the fossil remains of Bükkábrány - Antalfi, Eszter; Fehér, Sándor (Acta Biologica Szegediensis, 2013)
The unique remains of a 7.2-million-year-old forest consisting of Bald cypress and Coast redwood were found in the area of Bükkábrány in County Borsod-Abaúj-Zemplén of Hungary. The trees of the fossil remains comprising 16 stems, which were discovered in a lignite mine, were standing in their original locality, and preserved their original cellular structure. No petrification occurred, which is general characteristics of wood remains preserved for millions of years. What makes the findings unique is that they make it possible to carry out the traditional histological examination of the intact wood structure. The results of light and electron microscopic investigations definitely proved that in addition to Bald cypress, the wood species of the ancient forest remains also included Coast redwood. Today, the natural habitat of Coast redwood is definitely in North-America, but millions of years ago, they were also present in Europe including the Carpathian basin. The xylotomic analysis has unambiguously revealed that two of the investigated five trunks are Bald cypress (Taxodium distichum) or the already extinct Taxodioxylon germanicum, while the other three trunks are Coast redwood (Sequoia sempervirens) or a member of the already extinctfamily, the Sequoioxylon sp.